2022
DOI: 10.3390/diagnostics12081873
|View full text |Cite
|
Sign up to set email alerts
|

Classification Scheme of Heating Risk during MRI Scans on Patients with Orthopaedic Prostheses

Abstract: Due to the large variety of possible clinical scenarios, a reliable heating-risk assessment is not straightforward when patients with arthroplasty undergo MRI scans. This paper proposes a simple procedure to estimate the thermal effects induced in patients with hip, knee, or shoulder arthroplasty during MRI exams. The most representative clinical scenarios were identified by a preliminary frequency analysis, based on clinical service databases, collecting MRI exams of 11,658 implant carrier patients. The therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The results do not take into account the impact of low-frequency induction heating of metallic implants naturally caused by switched gradient fields. Important work on this subject matter has recently been reported in [21], [22], [23], [24], [25], [26], [27]. Unless an orthopaedic implant has a loop path, heating due to gradient fields is typically less than heating due to RF energy deposition.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…The results do not take into account the impact of low-frequency induction heating of metallic implants naturally caused by switched gradient fields. Important work on this subject matter has recently been reported in [21], [22], [23], [24], [25], [26], [27]. Unless an orthopaedic implant has a loop path, heating due to gradient fields is typically less than heating due to RF energy deposition.…”
Section: )mentioning
confidence: 99%
“…One major safety concern, relevant to both passive and active implants, is implant heating within MR radiofrequency and gradient coils [5], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The interaction between a metallic object implanted in a patient's body and MRI gradient fields has been analyzed in several papers, specifically dealing with the risk of heating. [10][11][12][13][14][15][16][17] Conversely, the possibility that such an interaction might alter the E-field distribution in native tissues surrounding the object, and its possible effects on PNS, has received little attention. Some authors published on investigations involving spinal fusion devices, 18,19 generic active implant electrodes, 20 and infusion pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency (RF) tissue heating has gained a wide attention both from the literature and relevant standards due to its potential to cause significant temperature increases when the incident RF field, implant characteristics, and exposure scenario meet specific criteria 11‐17 . While RF remains the most important source of heating in MRI, recent studies showed that heating induced by gradient fields could also represent a risk in the presence of bulky conductive objects 5,18,19 …”
Section: Introductionmentioning
confidence: 99%